2018
DOI: 10.1111/chd.12673
|View full text |Cite
|
Sign up to set email alerts
|

Utility of three-dimensional models in resident education on simple and complex intracardiac congenital heart defects

Abstract: Incorporation of 3D printed models into lectures about CHD imparts a greater acute level of understanding, both subjective and objective, for pediatric and combined pediatric/emergency medicine residents. There does not seem to be an added benefit for understanding ventricular septal defects, but there is for tetralogy of Fallot, likely due to increased complexity of the lesion and difficulty visualizing spatial relationships in CHD with multiple components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 18 publications
(36 reference statements)
6
83
0
3
Order By: Relevance
“…Their results showed that 3D-printed models enhanced residents' understanding and satisfaction during the teaching sessions when compared to 2D images, and increased their confidence in managing patients with ToF. Similar findings are reported by White et al (29) who divided 60 pediatric residents into two groups, 29 participating in the control group and 31 in the intervention group. Both groups received the same 20-min lecture including 2D images of ventricular septal defect (VSD) or ToF, while the intervention group was given 3D-printed models of normal hearts and each CHD.…”
Section: D-printed Models In Chdsupporting
confidence: 74%
See 1 more Smart Citation
“…Their results showed that 3D-printed models enhanced residents' understanding and satisfaction during the teaching sessions when compared to 2D images, and increased their confidence in managing patients with ToF. Similar findings are reported by White et al (29) who divided 60 pediatric residents into two groups, 29 participating in the control group and 31 in the intervention group. Both groups received the same 20-min lecture including 2D images of ventricular septal defect (VSD) or ToF, while the intervention group was given 3D-printed models of normal hearts and each CHD.…”
Section: D-printed Models In Chdsupporting
confidence: 74%
“…Studies support the clinical value of 3D-printed models in CHD, specifically with reported usefulness of 3D printing in pre-surgical planning and simulation of complex situations (9,18,(23)(24)(25). Although most of the current literature on 3D printing in CHD is dominated by case reports and case series, emerging evidence based on randomized controlled trials and multicenter studies further confirms its incremental value over traditional visualization tools (26)(27)(28)(29)(30)(31).…”
Section: D-printed Models In Chdmentioning
confidence: 79%
“…3D printed models derived from patient's imaging data are increasingly used in medical applications, with most of the studies focusing on the clinical value of patientspecific 3D printed models such as pre-surgical planning and simulation, medical education and patient-doctor communication (18)(19)(20)(21)(22)(23)29,30). A new research direction of clinical application of 3D printed models is to develop optimal CT scanning protocols for radiation dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Image processing and additive manufacturing technologies enable the creation of 3D models based on computer tomography (CT) or magnetic resonance imaging (MRI) scans and subsequently the printing of realistic threedimensional replicas of human hearts. 3D printed heart models are suitable for morphology courses (5)(6)(7)(8)(9)(10)(11)(12), education of nurses (13), surgical training (14)(15)(16)(17)(18)(19)(20), surgical planning (3) and patient education (21)(22)(23). The cardiac 3D replicas produced in this study have been successfully utilized in hands-on catheterization courses for students, residents and experienced cardiologists.…”
Section: European Pediatric Immediate Life Support (Epils) and Europementioning
confidence: 97%